Pituitary adenoma consistency: Direct correlation of ultrahigh field 7T MRI with histopathological analysis. Issue 126 (May 2020) - Yao, Amy; Rutland, John W.; Verma, Gaurav; Banihashemi, Amir; Padormo, Francesco; Tsankova, Nadejda M.; Delman, Bradley N.; Shrivastava, Raj K.; Balchandani, Priti
Highlights: Fifteen patients with pituitary adenomas were scanned at 7 T MRI. Tumors rated as soft were hyperintense to gray matter on 7 T T2-weighted imaging. Percentage of hyperintense tumor voxels and tumor collagen content were correlated. SI ratio was positively correlated with tumor cellularity and collagen content. Abstract: Purpose: Tumor consistency is a critical factor in surgical planning that influences ease of resection and risk of operative morbidity. The ability of MRI to predict tumor consistency tumor consistency has been shown to increase with higher field strength. The present study examined the utility of 7 T (7 T) MRI in predicting the tumor consistency of pituitary adenomas. Method: Fifteen patients with pituitary adenomas were preoperatively scanned at 7 T MRI. Regions of interest were drawn around lesions for voxel-based signal intensity (SI) analysis. The percentage of tumor voxels with intensity higher than local gray matter was calculated on T2-weighted imaging. A single neurosurgeon rated tumor firmness for all patients. Histopathological analysis was performed. Radiological tumor features were correlated with intraoperative tumor consistency measurements and histopathology. Results: Tumors rated as 'soft' intraoperatively were hyperintense to local gray matter on T2-weighted imaging. 'Firm' tumors were hypointense to local gray matter. There was no significant difference in SI ratio between soft and firm tumors (p = 0.098). Soft tumors had a significantly higher percentage of tumor voxels greater than local gray matter compared to firm tumors (p = 0.035, Cohen's D-effect size = 1.208). Soft tumors had higher vascularity than firm tumors, p = 0.015. Conclusions: The signal and contrast advantage conferred by 7 T MRI may provide valuable preoperative information regarding pituitary tumor consistency and physiology. The use of granular, voxel-based analysis maximizes the potential afforded by the high resolution of 7 T imaging, and may be a valuable method of predicting consistency of pituitary adenoma.